Problematika Guru Pendidikan Agama Islam dalam Pembinaan Akhlak Siswa SD Negeri 18 Kota Padang - Ulawal, Romi; Satria, Rengga (FONDATIA, 2023)
Every activity or action carried out by humans must find various problems in it, including problems in the moral development of students in elementary schools. The purpose of this study was to find out how the problems of PAI teachers are in fostering morals in elementary school students. This study uses a qualitative method with a descriptive approach. researchers conducted research at SD Negeri 18 Padang City. Sources of data were taken through direct interviews with three informants. The informants consisted of school principals, PAI teachers and class teachers. The data collection techniques used are observation, interviews and documentation. All interview results were analyzed thematically using the Miles and Huberman technique. While testing the validity of the data using a credibility test with increased persistence and triangulation. The research findings found that the problems in fostering student morals in elementary schools came from external and internal factors. Problems that arise due to external factors are the family environment and social environment. Problems that arise due to internal factors are the lack of PAI teachers in teaching religious knowledge and instilling noble moral values in students. Not only that, there are still teachers who break the rules, such as arriving late and speaking in a high tone.